A Changing Spectrum of Colorectal Cancer Biology With Age: Implications for the Young Patient. Issue 1 (January 2019) - Chouhan, Hanumant; Ferrandon, Sylvain; DeVecchio, Jennifer; Kalady, Matthew F.; Church, James M.
Abstract : BACKGROUND: The methylator pathway of colorectal carcinogenesis, characterized by CpG island hypermethylation and BRAF mutations, accounts for ≈25% of colorectal cancers. Because these cancers tend to be right sided and because DNA methylation in the right colon increases with age, we expect an increasing proportion of right-sided cancer over time. Conversely, we expect young patients (age <50 y) to have less methylated and fewer right-sided cancers OBJECTIVE: The purpose of this study was to analyze the distribution and genetic traits of colorectal cancer from different age groups. DESIGN: This was a retrospective cohort study. SETTING: The study was conducted at a high-volume tertiary referral center. PATIENTS: Patient samples included those from our colorectal cancer biobank of resected colorectal cancer specimens. MAIN OUTCOME MEASURES: Tumor CpG island hypermethylation, microsatellite instability, and mutations in KRAS and BRAF oncogenes were analyzed in resected specimens and stratified by age and tumor location. Comparisons included age >50 or <50 years and decade of diagnosis (⩽50, 51–60, 61–70, 71–80, and >81 y). Patients with IBD or hereditary syndromes were excluded. RESULTS: A total of 497 colorectal cancers were analyzed (266 men and 231 women); 57 patients (11.5%) were ⩽50 years of age. No young cancers (0/57) were hypermethylated compared with 97 (22%) of 440 cancers of patients aged >50 years ( p < 0.001). An increasing percentage of tumors were CpG island phenotype high with each decade of age at diagnosis. No cancers in patients <50 years of age were microsatellite unstable compared with 91 (23.6%) of 346 for those >50 years of age. No young cancers contained a BRAF mutation compared with 46 (10.6%) of 434 in older cancers ( p < 0.001). KRAS mutations were less common in young cancers compared with older cancers (13/57 (22.8%) vs 126/410 (30.7%); p < 0.01). Eleven (19.3%) of 57 young cancers were proximal compared with 228 (51.8%) of 440 ( p < 0.001) older cancers. LIMITATIONS: This study was limited by its retrospective design. CONCLUSIONS: The lack of CpG island methylator phenotype tumors in young patients is consistent with the dominant left-sided cancer distribution seen in the young and focuses efforts to understand and prevent cancer in this age group on causes of chromosomal instability. SeeVideo Abstract athttp://links.lww.com/DCR/A709 .